Comparative study of structure and photo-induced reactivity of malonaldehyde and acetylacetone isolated in nitrogen matrices: Molecular Solids - Trivella, A.; Coussan, S.; Chiavassa, T.; Theulé, P.; Manca, C.; Roubin, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Structure and reactivity of the eight enolic forms (one chelated and seven non-chelated) of malonaldehyde and acetylacetone are compared through theoretical and experimental data. Ground-state geometries, energies, and vibrational frequencies are calculated with the B3LYP/6–311++G(2d, 2p) model chemistry. The electronic delocalisation as well as the cis/trans rotamer properties are analysed. The hydrogen bond strength of the chelated forms can be estimated by the energy difference between chelated and non-chelated forms, and its enhancement due to methyl-induced electron release is estimated at 1.7 kcal·mol–1. UV- and IR-induced reactivity of molecules isolated in nitrogen matrices is studied by means of FT–IR spectrometry. Interconversion between rotamers is the main process observed for both molecules, only some among the seven non-chelated forms being created.